2004
DOI: 10.1021/jo049880g
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Mild, and Facile Method To Prepare 6-Methylidene Penem Derivatives

Abstract: A novel and mild method was established to synthesize 6-methylidene penem compounds. This method entails a MgBr(2)/Et(3)N-promoted aldol-type condensation on 6-bromopenem 12 with an appropriately substituted aldehyde to yield the intermediate acetylated bromohydrin, which was smoothly converted to the final product with simultaneous deprotection of C3 carboxylic acid ester using activated zinc dust and phosphate buffer at pH 6.5. This process provides a useful variation of C-C bond formation method for penem d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Of particular interest in this study, another amido reagent, the thermally highly stable lithium diphenylamide (LiNPh 2 ), has shown promise in a range of synthetic transformations. As well as regioselective deprotonation reactions, [6][7][8][9][10] it has also been used in catalytic aldol reactions involving silyl enol ethers and aldehydes; [11,12] in elimination applications; [13,14] in metathetical reactions; [15][16][17][18][19][20][21][22][23][24][25][26][27] during the preparation of amino-containing carbenes, [28] and as an initiator in the polymerisation of methyl methacrylate. [29] utilised as the metallating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest in this study, another amido reagent, the thermally highly stable lithium diphenylamide (LiNPh 2 ), has shown promise in a range of synthetic transformations. As well as regioselective deprotonation reactions, [6][7][8][9][10] it has also been used in catalytic aldol reactions involving silyl enol ethers and aldehydes; [11,12] in elimination applications; [13,14] in metathetical reactions; [15][16][17][18][19][20][21][22][23][24][25][26][27] during the preparation of amino-containing carbenes, [28] and as an initiator in the polymerisation of methyl methacrylate. [29] utilised as the metallating agent.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed our experience has shown that charge and spin densities (q and ρ, respectively) calculated by using the B3LYP method are of sufficiently high quality to explain the reactivity of 2,2′,3,3′-tetraphenylbicyclopropenyl radical cations [restricted B3LYP/6-31G(p)], [63] the molecular geometries and electronic structure of the geminally diphenyl-substituted trimethylenemethane radical cation [64] and 1,4-diphenylcyclohexane-1,4-diyl radical cation (5 •+ ) [65] (UB3LYP/cc-pVDZ), and the classical and nonclassical radical ions derived from 7-benzhydrylidenenorbornene analogs, [66][67][68] in addition to other reactive intermediates of this type. [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] RESULTS AND DISCUSSION σ*-π* Conjugation of silole…”
Section: Methodsmentioning
confidence: 99%
“…Reaction between (5R, 6S)-6-bromo-7-oxo-4-thia-1-azabicycloA C H T U N G T R E N N U N G (3.2.0)hept-2-ene-2-carbocylic acid 4-nitrobenzyl ester 7 and aldehydes 8 a-h followed by a reductive elimination/deprotection step produced penems 9 a-h with Z configuration [23] (Scheme 1). The desired 5,5-bicyclic aldehydes 8 a-h required for these transformations were synthesized by utilizing different methods as described previously.…”
mentioning
confidence: 99%